Iscenesættelse som tilsynebringelse - Seel, Martin (Peripeti, 2021)
In »Staging as appearing-making« (originally: »Inszenieren als Erscheinenlassen«, 2001) Seel presents an understanding of staging, including a compact definition of the concept, by which he demarcates it as a special aesthetic phenomenon that nevertheless is not reserved for the art or the theatre alone.